P-35 Health care assistants complement palliative care teams – influencing end of life care for patients in the community. Issue Volume 5: Issue (2015)Supplement 3 (1st November 2015) - Richardson, Fay
Abstract : Marie Curie (March 2012) promotes senior HCAs roles within palliative care services, providing a robust service dealing with challenges of crisis and avoiding hospital admission for patients with life limiting illness. The introduction of HCAs to a hospice community team demonstrates how this growing diverse role supports the theory that appropriate multi-disciplinary care creates resilience, influences place of death and avoids hospital admission. Aims: To support patients at home, die in their preferred place of care reducing hospital admissions. To promote resilience in patients and carers. To create a sustainable services providing appropriate levels of care to greater number of patients/carers. Approach: Recruiting two part-time HCAs to the community palliative care team supporting patients in outpatient's services and at home. A robust competency and mentor support programme was implemented to enable HCAs to provide lone working visits, supporting patients and carers in many ways e.g. personal care, hand massage, support sits. Outcomes: HCA support lone working visits and support telephone calls have grown as their confidence and competence is established. In the last 3 – 6 months number of patients dying at home has increased from 9 to 19 and the number of hospital admissions resulting in death has decreased from 15 to 9. Hospice admissions remained unchanged. The number of community nursing team referrals increased from 20 in September 2014 to 31 in March 2015. Conclusion: The HCA role has provided a more balanced service in terms of the appropriate level of HCP visiting a patient, creating greater opportunity for supporting larger numbers of referrals by working more efficiently. They have increased the ability to provide appropriate care to meet needs of a patient in a crisis situation. Anecdotally the support provided has maintained patients and carers resilience to stay at home. By the conference date questionnaire to audit this service will have beencompleted for service users and professionals.